753 Outcomes of Bariatric Surgery in Patients with Inflammatory Bowel Disease and the Development of De-Novo IBD Following Bariatric Surgery: A Systematic Review. (19th August 2022) - Mian, A; Khan, S
Abstract: Aim: A large proportion of patients with inflammatory bowel disease are obese. Outcomes of bariatric surgery in patients with IBD and on IBD disease course itself is not clear. Furthermore, there is some evidence that bariatric surgery can precipitate the development of De-novo IBD. Thus, the aim of this systematic review was to search the literature to summarise the evidence surrounding these questions. Method: A comprehensive literature review was conducted based on the preferred reporting items for systematic reviews and meta-analysis guidelines (PRISMA). PUBMED, and MEDLINE databases was searched using Ovid for keywords and MeSH terms including "gastric bypass", "sleeve gastrectomy", "Roux-en-Y", "Duodenal switch", "RYGB", "bariatric surgery" and "inflammatory bowel disease", "IBD", "Crohn's disease", "Ulcerative colitis", "UC". Prospective and retrospective studies published up to March 2021 were included in this systematic review. Results: 22 studies met the inclusion criteria. Studies revealed that bariatric surgery is safe for patients with IBD and leads to comparable outcomes to patients without IBD. Some studies showed that patients with IBD remained in hospital for slightly longer periods of times than non IBD patients with a modest increase in the number of complications. Furthermore, studies suggest bariatric surgery may lead to the development of de-novo IBD in a selection of patients. Conclusion: Bariatric surgery is effective for patents with IBD reporting significant weight loss at both the 6 and 12-month time points. Further studies are needed to more accurately determine if bariatric surgery can predispose to the development of De-Novo IBD in a select group of patients.